The impact of different industry-education integration models on corporate financial performance - Lingli Zou; Nelson Lajuni; Mathew Kevin Bosi (Human Resource Management Academic Research Society, 2025)
Industry-education integration is vital for fostering global economic advancement and corporate progress. This study examines the effect of several industry-education integration models on the financial performance, utilizing cross-sectional data from 166 publicly listed Chinese companies in 2022. The findings indicate that the transfer of human resources markedly enhances all financial metrics. Scientific publications, intellectual property, informal idea sources, and research services often positively influence many financial metrics. The findings regarding the influence of research partnerships on financial performance are contradictory. The findings emphasize the disparities in the efficacy of various industry- education integration models, highlighting the need for focused collaborative strategies to enhance firm performance and provide practical insights for firms seeking to develop industry-education integration strategies.